How do physicians and their partners coordinate their careers and private lives? (Swiss Medical Weekly, 2011)
QUESTIONS UNDER STUDY: Over the past few years, there has been increasing interest in the question of how couples coordinate their careers and private lives. The aim of this study was to investigate the career arrangements of physicians and their partners according to gender and parenthood status, and to compare dual-physician couples with other types of couples. METHODS: Data pertaining to 414 physicians (214 females, 51.7%; 200 males, 48.3%) from a cohort of medical school graduates participating in the SwissMedCareer Study was analysed according to socio-demographic variables, employment status and career prioritisation of the physicians and their partners. Differences in terms of gender, parenthood status and type of couple were investigated with Chi-square tests. RESULTS: The most prevalent career arrangement for a male physician with young children was that of full-time employment for the physician himself with a partner not in employment or working less than 50%-time. By contrast, the most common arrangement for a female physician with young children was that of 50–69% part-time employment with a partner working full-time. For couples without children, the most common arrangement was full-time employment for both partners. Dual-physician couples differed significantly from other types of couples in terms of how they rated career priority, with male physicians with physician partners more likely than male physicians with partners holding another academic degree or with non-academic partners to regard both careers as equally important (p ≤0.001). Female physicians with physician partners were more likely to consider their partners’ careers as of prime importance than those with academic or non-academic partners (p ≤0.001). CONCLUSION: The priority given by couples to the man’s career reflects traditional gender-role attitudes in male and female physicians. Starting a family slows down the career progress of female physicians but not of male physicians. Providing more childcare facilities in hospitals and flexible working hours to meet the needs of physician parents with young children could encourage a higher work participation of physician-mothers and might constitute an effective strategy for combating the shortage of physicians in Switzerland.